1994
DOI: 10.2307/3869677
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Protein Expression in Plant Mitochondria

Abstract: Although the physiological role of plant mitochondria is thought to vary in different tissues at progressive stages of development, there has been little documentation that the complement of mitochondrial proteins is altered in different plant organs. Because the phenomenon of cytoplasmic male sterility suggests an unusual function for mitochondria in floral buds, we examined the tissue-specific expression of mitochondrial proteins in petunia buds at several stages of development, using both fertile and cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…A few publications cover the problem of copy numbers and expression of mitochondrial genes in different plant tissues and in relation to different developmental stages of plant organs (Newton and Walbot, 1985;Topping and Leaver, 1990;Borner and Hess, 1993;Conley and Hanson, 1994;Huang et al, 1994;Smart et al, 1994). In this work the effects of light and acetate on the expression of the mitochondrial cob gene coding for the apocytochrome b were investigated.…”
Section: Schaftmentioning
confidence: 99%
“…A few publications cover the problem of copy numbers and expression of mitochondrial genes in different plant tissues and in relation to different developmental stages of plant organs (Newton and Walbot, 1985;Topping and Leaver, 1990;Borner and Hess, 1993;Conley and Hanson, 1994;Huang et al, 1994;Smart et al, 1994). In this work the effects of light and acetate on the expression of the mitochondrial cob gene coding for the apocytochrome b were investigated.…”
Section: Schaftmentioning
confidence: 99%
“…A second explanation for pollen specificity could be increased levels of a toxic protein in tapetal tissue or sporogenous tissue. Expression of wild-type mitochondrial proteins and mitochondrial transcripts varies between different tissues in the plant (Conley and Hanson, 1994;Moneger et al, 1994), so aberrant proteins could possibly change in concentration during anther development. However, it is technically difficult to distinguish whether the concentration of a protein within a mitochondrion has changed in young anthers or whether apparently enhanced levels of a mitochondrial protein are an indirect result of an increase in mitochondrial number, which has been documented in the tapetum and wild-type sporogenous tissue of maize (Warmke and Lee, 1978).…”
Section: A Special Role For Mitochondria In Pollen Development?mentioning
confidence: 99%
“…Both the expression and tissue location of the alternative oxidase, however, appear to be developmentally regulated. Levels of alternative oxidase proteins increase dramatically during the development of thermogenesis (Rhoads and McIntosh, 1992) and, furthermore, appear to be expressed to different extents in shoots and roots of nonthermogenic tissues (Kearns et al, 1992;Conley and Hanson, 1994). More recently Umbach and Siedow (1993) and Umbach et al (1994) have shown that the alternative oxidase can exist in both a reduced and an oxidized form within the mitochondrial membrane and the two forms are interconvertible by addition of reducing and oxidizing agents, respectively.…”
mentioning
confidence: 99%